KAJIAN PUSTAKA: PEMICU KANKER DALAM SATE, AYAM/BEBEK/IKAN BAKAR/GORENG DAN ABON - Djalal Rosidi; Lilik Eka Radiati; Warsito Warsito; Eko Saputro (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Indonesian people are very fond of consuming satay, grilled/ fried chicken/ duck/ fish because these are very delicious but consumers still do not understand that there are carcinogenic consequences of heterocyclic aromatic mines (HAA) and polycyclic aromatic hydrocarbons (PAH) which are harmful to health. This paper aims to explore HAA, PAH and various ways that have succeeded in minimizing these levels so that consumers can still enjoy these foods safely and comfortably. Thermal meat processing is an important process to ensure microbiological safety, eliminate antinutrical factors, improving digestibility and bioavailability of nutrients and develop the profile of the color, aroma and flavor attributes that we want. However, this process also turns out to bring about carcinogens (cancer triggers), HAA and PAH that are potentially harmful to our health in the long run. The results of this literature review provide practical information that can be applied by producers or housewives to minimize HAAs levels in finished products, which is choosing the right sugar for marination; addition of synthetic antioxidants; addition of natural antioxidants; addition of phytochemical and herbal extracts; and pretreatment using a microwave.